Detecção de herpesvírus bovino 5 (BoHV-5) em bovinos do Sudeste Brasileiro - Gomes, L. I.; Rocha, M. A.; Costa, E. A.; Lobato, ZIP; Mendes, LCN; Borges, A. S.; Leite, R. C.; Barbosa-Stancioli, E. F. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2002)
This paper reports the detection of bovine herpesvirus type 5 (BoHV-5) by a specific nested PCR assay. Samples were collected from the central nervous system (CNS) of cattle from Minas Gerais and São Paulo States, Brazil. All animals died presenting neurological symptoms. Nineteen frozen CNS samples analyzed had been previously tested by fluorescence antibody test for rabies virus and showed negative results. Three paraffin-embedded brain tissue samples were examined by histopatology and the observed alterations suggested nonsuppurative meningoencephalitis. BoHV-5 was detected in five (22.7%) among 22 tested samples. The occurrence of BoHV-5 infection is reported in the Southeast region of Brazil, indicating that epidemiological studies should be carried out.
Detection of bovine herpesvirus type 5 (BoHV-5) in cattle in Southeast Brazil
Keywords: bovine herpesvirus type 5; meningoencephalitis; nested PCR; rabies